Interpretasi Audiens pada Pasangan Suami Istri dalam Program KB Vasektomi di Youtube Channel Kang Dedi Mulyadi : (Analisis Resepsi pada Masyarakat Klapanunggal, Bogor) - Muhammad Rifai; Nawiroh Vera (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The development of digital media, especially YouTube, has become an important tool in disseminating social issues, including the Family Planning (FP) program. One of the contents that has attracted public attention is a video on Kang Dedi Mulyadi's YouTube channel entitled "Father of 11 Children Asks for Time for Istikharah When KDM Invites to Use KB," which raises the invitation to perform vasectomy as a form of male responsibility in birth control and family economic readiness. This study aims to analyze the reception of the message conveyed in the video by the Klapanunggal community, Bogor Regency. The study used a descriptive qualitative approach with a constructivist paradigm and the Stuart Hall reception analysis method. Data were obtained through observation, in-depth interviews, and documentation of 10 informants consisting of 5 married couples. The analysis was conducted using the Stuart Hall encoding ecoding model that groups the audience into Dominant, Negotiated, and Oppositional positions. The results showed that the audience's interpretations were diverse, with 4 informants in the Dominant position, 2 informants in the Negotiated position, and 4 informants in the Oppositional position. Differences in reception were influenced by factors such as religion, culture, education, personal experience, and knowledge about vasectomy. The study concluded that the video was effective in sparking public discussion, but it did not yet produce a consensus on a dominant meaning within the community.